Irony and Black Comedy in the Animal Kingdom: La Divina Chusma (The Divine Rabble) by Rafael Ángel Herra, or a Revision of the Traditional Fable (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2017)
This study focuses on the analysis of the collection of fables La divina chusma, by the writer and philosopher Rafael Angel Herra (Costa Rica, 1943), published in 2011. We will try to demonstrate how the volume relates to the classical models (Aesop, Phaedrus) and to the ones from the 18th century (La Fontaine, Iriarte, Samaniego), while it suggests a revisit to the genre from a parodic point of view that does not abstain from the use of irony and black humor. To achieve our goal, we propose, at first, a reading from the tradition of the genre of the fable, through a study of intertexts and the role of the fable in historical contexts from the Greco-Roman era to the stage of the Spanish Ilustración. Regarding the theory that we use as a research support, we propose a link between consolidated literary theories (from Vladimir Propp) and other theories of current interest, such as Omar Calabrese's reflections on the recovery of aesthetic and artistic products of the past, or the studies of David Le Breton on the need of human beings to escape social pressure (with an application, of course, to the animal world), or – finally – Bruno Bettelheim's research into the psychoanalytic meanings of fables.Key words: Rafael Angel Herra, Costa Rican Contemporary Literature, La divina chusma, genre of fable.